The effects on ruminal pH and serum haptoglobin after feeding a grain-based supplement to grazing dairy cows as a partial mixed ration or during milking. Issue 1 (April 2015) - Coombe, J.E.; Pyman, M.F.; Mansell, P.D.; Auldist, M.J.; Anderson, G.A.; Wales, W.J.; Conley, M.J.; Manos, S.; Hannah, M.; Fisher, A.D.
Highlights: Grazing cows fed supplement during milking or as a partial mixed ration on a feedpad. Ruminal pH and serum haptoglobin (Hp) concentrations were measured. Supplement feeding method did not affect ruminal pH or serum Hp. Abstract: Ruminal pH and serum concentrations of haptoglobin (Hp) were measured in order to assess the risk of subacute ruminal acidosis (SARA) in grazing cows offered rolled wheat grain twice daily in the dairy at milking (Control group; n   =  64), or as a partial mixed ration (PMR group; n   =  64) on a feedpad. Cows were allocated various levels of the supplement (8, 10, 12 or 14 kg dry matter/day). Ruminal pH was measured in 16 rumen-fistulated cows (eight PMR and eight Control group cows), using indwelling pH meters, recording every 10 min for 14 days. Serum Hp was analysed in samples collected from 125 cows. No differences in ruminal pH or serum Hp concentration were found between treatment groups, or levels of feeding. It was concluded that, using ruminal pH patterns and Hp as markers of SARA at the feeding levels used in this study, there were no differences between grazing cows fed the supplement either as grain in the dairy or as a PMR fed on a feedpad.